PRACTICE OF USING VIRAL PROTEASE INHIBITORS IN CHILDREN WITH HIV INFECTION - V.B. Denisenko; E.N. Simovan'yan; E.V. Beketova (Union of pediatricians of Russia, 2010)
Selection of the most effective and safest high-active antiretroviral therapies is a critical issue faced by modern HIV medicine. Authors studied 28 children with HIV infection aged from 3 to 7 divided into two groups administered a combination of two HIV reverse transcriptase nucleoside inhibitors with viral protease nelfinavir inhibitors (n = 13) and lopinavir/ritonavir (n = 15). The subjects in both groups demonstrated a decreased frequency of HIV-associated symptoms and opportunistic infections, positive dynamics of immunological indicators, suppression of HIV replication. When lopinavir/ritonavir was administered, there was more even better dynamics in clinical, immunological and virologic parameters, which allows this medication to be recommended as a antiretroviral therapy for children. Key words: HIV infection, lopinavir/ritonavir, nelfinavir, children. (Pediatric Pharmacology. - 2010; 7(1):62-67)